2008
DOI: 10.1089/ast.2006.0037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Morphological Biosignatures in Martian Analogue Field Specimens Using In Situ Planetary Instrumentation

Abstract: We have investigated how morphological biosignatures (i.e., features related to life) might be identified with an array of viable instruments within the framework of robotic planetary surface operations at Mars. This is the first time such an integrated lab-based study has been conducted that incorporates space-qualified instrumentation designed for combined in situ imaging, analysis, and geotechnics (sampling).Specimens were selected on the basis of feature morphology, scale, and analogy to Mars rocks. Two ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Furthermore, the evidence provided here on the composition and origin of the ovoid structure in Nakhla indicates that clays were also forming on Mars more recently than the Early Hesperian (i.e., during the Amazonian), which is a trend also reflected to some degree by recent MSL Curiosity rover results (Vaniman et al, 2014). Ultimately, the detailed microtextural, structural, mineralogical, and chemical investigation of martian meteorites provides a valuable tool for evaluating the biogenicity of possible microscopic morphological biosignatures identified during future astrobiology missions to Mars and provides a roadmap outlining the instruments with which they could be studied (Pullan et al, 2008). Furthermore, these studies may also be useful for assessing the possible habitability of the martian subsurface, both in the distant past and in the more recent geological history of Mars.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the evidence provided here on the composition and origin of the ovoid structure in Nakhla indicates that clays were also forming on Mars more recently than the Early Hesperian (i.e., during the Amazonian), which is a trend also reflected to some degree by recent MSL Curiosity rover results (Vaniman et al, 2014). Ultimately, the detailed microtextural, structural, mineralogical, and chemical investigation of martian meteorites provides a valuable tool for evaluating the biogenicity of possible microscopic morphological biosignatures identified during future astrobiology missions to Mars and provides a roadmap outlining the instruments with which they could be studied (Pullan et al, 2008). Furthermore, these studies may also be useful for assessing the possible habitability of the martian subsurface, both in the distant past and in the more recent geological history of Mars.…”
Section: Discussionmentioning
confidence: 93%
“…In this respect, the diagnosis, catagenesis and biodegradation of terrestrial Mars analogues to give the fossils recognizable in our own geological record would not be transposable to a Martian scenario. Hence, the complex chemical systems comprising terrestrial soils, bitumens and kerogens found in our own planetary lithology [25][26][27] and which provide much valuable information about their sourcing processes would not be expected to occur to the same extent on Mars. However, it is believed that Mars might still preserve a chemical record of early life in rocks from the Noachian era, which overlaps the terrestrial Archaean geological history, from about 3.8 Gya.…”
Section: (A) Analytical Astrobiology Of Marsmentioning
confidence: 99%
“…Additionally, the breakdown products of chlorophyll and porphyrins have been identified as stable and geologically persistent molecules (Baker & Louda 1986;Parnell et al 2007) that are detectable using a variety of methods (Suo et al 2007). While chlorophyll in exposed cyanobacteria is susceptible to degradation by ionizing radiation and loses is spectral properties (Dartnell et al 2011), the role of an endolithic niche and mineral shielding has yet to be explored with UV/VIS reflectance spectroscopy, as most work was focused on Raman and infrared (IR) spectroscopy (Wynn-Williams et al 2002;Marshall et al 2006;Pullan et al 2008;Foster et al 2010). The UV/VIS (300-2500 nm) spectral region is relevant as it corresponds to the wavelengths (* 400-1000 nm) of MER's Pancam, MSL's Mastcam and the proposed spectroscopic cameras for the ExoMars mission (Table 1) (Bell et al 2003;Cousins et al 2010Cousins et al , 2012, and pigments such as chlorophyll absorb strongly in the visible spectrum and have unique spectral signatures (Berg et al 2002).…”
Section: Spectroscopy Of Biomarkers and Chlorophyllmentioning
confidence: 99%